Figurative Language Found in the Life Support Album by Madison Beer - Jaya, Made Dhaniswara; Komang Dian Puspita Candra; Desak Putu Eka Pratiwi (Journal of Language and Applied Linguistics, 2024)
The study aims to identify the many types of figurative language found in Madison Beer's album Life Support. Knickerbocker and Reninger's (1974) theory was employed to determine the figurative language found in Madison Beer's album Life Support. The information was gathered through downloading and listening to each song on the Life Support album, as well as reading up and taking notes on the lyrics. The data were analyzed using a qualitative method. Madison Beer's Life Support album contains eight out of ten types of figurative language, according to the study's findings. There are 12 data in simile, four data in personification, metaphor, irony, and metonymy, three data in synecdoche, and two data in each type of metaphor and paradox. A simile with 12 facts is the most prevalent figurative language used in Madison Beer's Life Support Album.